Kreatywność w marketingu jako podstawa sukcesu rynkowego - koncepcja, współzależności, problemy metodyczne - Styś, Aniela; Kłeczek, Ryszard; Wrona, Sylwia (Creativity in Marketing as a Base of Market Success - Concept, Interrelationships and Methodological Questions, 2006)
The authors pay attention to creativity of marketing and present the findings of the research which concern the creativity and market success. The authors of the article also investigate how to measure relationship between conditions, and market effects of creativity in marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 351-361